Leveraging Medical Terminologies via a Multi-Terminology Server to Enhance the Interoperability in Dedalus Solutions...20th World Congress on Medical and Health Informatics (MEDINFO), August 9-13, 2025, Taipei, Taiwan - YASINI, Mobin; RAUSCH, Dennis; FLEMING, Dougal; JAYARAMAN, Deepthi; WILLAERT, Milan; VARGHESE, Jince Tom; DAHLWEID, Michael (Studies in Health Technology & Informatics, 2025)
Achieving interoperability across healthcare systems is essential for improving healthcare delivery. Medical terminologies such as SNOMED CT, LOINC, and ICD play a pivotal role in standardizing clinical data, yet their integration into complex platforms remains challenging. This study evaluates the implementation of Ontoserver, a clinical terminology server based on HL7 FHIR, within Dedalus's software ecosystem to address these challenges. Technical enhancements, including the deployment of a sidecar FHIR resource server and workflow automation tools, facilitated efficient terminology management. A case study on Dedalus's "Trial for Care" platform highlighted the use of Ontoserver's concept mapping and exploration features to automate the standardization of bespoke codifications. Results showed improved data interoperability, reduced manual effort, enhanced data usability, and streamlined workflow transitions. While challenges such as managing regional standards and optimizing mappings persist, this study underscores the transformative potential of Ontoserver in achieving smarter interoperability and advancing healthcare outcomes.